Diversity of laccase-coding genes in Fusarium oxysporum genomes - Kwiatos, Natalia; Ryngajłło, Małgorzata; Bielecki, Stanisław (Frontiers in Microbiology, 2015)
Multiple studies confirm laccase role in fungal pathogenicity and lignocellulose degradation. In spite of broad genomic research laccases from plant wilt pathogen Fusarium oxysporum are still not characterized. The study aimed to identify F.oxysporum genes that may encode laccases sensu stricto and characterize the proteins in silico in order to facilitate further research on their impact on the mentioned processes. Twelve sequenced F.oxysporum genomes available on Broad Institute of Harvard and MIT website were analyzed and 3 genes that may encode laccases sensu stricto were found. Their amino acid sequences possess all features essential for their catalytic activity, moreover, the homology models proved the characteristic 3D laccase structures. The study shed a light on Fusarium oxysporum as a new source of multicopper oxidases, enzymes with possible high redox potential and broad perspective in biotechnological applications.